Molecular cytogenetic delineation of the critical deleted region in the 5q- syndrome. - Jaju, R; Boultwood, J; Oliver, F; Kostrzewa, M; Fidler, C; Parker, N; McPherson, J; Morris, S; Müller, U; Wainscoat, J; Kearney, L (1998)
The 5q- syndrome is a distinct type of myelodysplastic syndrome (MDS) characterised by refractory anaemia, morphological abnormalities of megakaryocytes, and del(5q) as the sole cytogenetic abnormality. In contrast to patients with therapy-related MDS with 5q deletions, 5q- syndrome patients have a favourable prognosis and a low rate of transformation to acute leukaemia. We have previously delineated a common deleted region of 5.6 Mb between the gene for fibroblast growth factor acidic (FGF1) and the subunit of interleukin 12 (IL12B) in two patients with 5q- syndrome and small deletions, del(5)(q31q33). The present study used fluorescence in situ hybridisation (FISH) analysis of these and a third 5q- syndrome patient with a small deletion, del(5)(q33q34), to refine further the critical deleted region. This resulted in the narrowing of the common deleted region within 5q31.3-5q33 to approximately 3 Mb, flanked by the adrenergic receptor beta 2 (ADRB2) and IL/2B genes. The common region of loss in these three 5q- syndrome patients includes the macrophage colony-stimulating factor-1 receptor (CSF1R), secreted protein, acidic, cysteine-rich (SPARC), and glutamate receptor (GR1A1) genes. This 5q- syndrome critical region is telomeric to and distinct from the other critical regions on 5q associated with MDS and acute myeloid leukaemia.